2021
DOI: 10.1186/s41983-021-00407-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in Parkinson’s disease patients: hospital-based study

Abstract: Background Parkinson’s disease (PD) is one of the most common neurodegenerative diseases. There is accumulating evidence that link gut microbiota to symptomatology and pathophysiology of PD. The aim of this study was to describe the pattern of gut microbiota and its association with PD and identify the effect of environmental factors on gut microbiota. This case–control study included 46 patients diagnosed as Parkinson’s disease (PD) and 31 healthy volunteers age and sex matched. Detailed histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Additionally, some studies generated contradictory outcomes. Akkermansia was found to be elevated in constipated PD patients in two studies [ 49 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies generated contradictory outcomes. Akkermansia was found to be elevated in constipated PD patients in two studies [ 49 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that PD should be considered a syndrome rather than a homogeneous disease, due to its varied manifestation among PD patients [ 80 ]. Although it is possible that patients with different PD phenotypes share specific microbiome signatures, the results from the studies investigating distinct PD subtype pathogens are incompatible with one another [ 33 , 34 , 37 , 41 , 43 , 58 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variations might contribute to the pathogenesis of PD by decreasing the production of short-chain fatty acids, the metabolism of lipids, immunoregulatory activity, and the permeability of the intestinal tract (Shen et al, 2021). A study conducted at an Egyptian hospital found that the PD group had considerably higher levels of lactic acid bacteria, Clostridium cluster IV, Akkermansia, Bifidobacterium, and a lower level of Firmicutes than the control group (Khedr et al, 2021) A previous meta-analysis found that probiotic intervention significantly improved motor symptoms, constipation, quality of life (QoL), anxiety, and depression parameters in PD patients (Park et al, 2023;Xie et al, 2023). Additionally, probiotic supplements boosted glutathione levels (GSH) in the serum of PD patients and decreased their reliance on laxatives.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of lactate production pathway is consistent with the increase of lactic acid bacteria (LAB) in PD patients 9 . However, the role of lactate in the pathogenesis of PD remains unclear 49 , as it appears to conflict with the health-promoting effects of LAB. One possibility is that lactate might be further metabolized by other bacteria (e.g., non-butyrate-producing lactate-utilizing bacteria) and finally convert to the products that might be detrimental to gut health (e.g., disrupt gut barrier) 50 .…”
Section: Discussionmentioning
confidence: 99%